Long Storage as Water Source during Dry Period for Sarawak River Basin - Nyambar, S. (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The recent drought in August 2009 which was triggered by the El Nino phenomenon had affected Kuching City to the extent that the city was facing critical shortage of water supply. In this study, the daily water demand for Kuching city was determined based on two major usages which were treated water demand for water supply production and for the flushing operation by the barrage in Sarawak River Basin for selected year.